Metallurgical process with nickel or cobalt alloys for the manufacture of semiconductor devices
Patent Information
- Application Number
- JP2024541056
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-07
- Filing Date
- 2023-02-07
- Publication Date
- 2025-02-21
Smart Images

Figure 2025505102000001 
Figure 2025505102000002 
Figure 2025505102000003
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of semiconductors, including dynamic random access memories (DRAMs), integrated circuits, and three-dimensional devices such as three-dimensional vertical NAND storage memories (3D-NAND). [Background technology]
[0002] Dynamic Random Access Memories consist of transistor cells and capacitors based on Metal-Oxide-Semiconductor (MOS) technology. The capacitors are usually MIM (Metal-Insulator-Meta) capacitors, consisting of two U-shaped electrodes, the top and bottom electrodes, separated by a dielectric material. The electrodes are based on metal oxides (i.e. RuO2 and SrRuO3, SnO2 and MoO2) or metals (i.e. Pt, TiN, TaN, Ru-Pt, Ta doped with SnO2). The dielectrics can be, for example, Al2O3, TiO2, ZrO2, HfO2, SrTiO3 (STO) or BaSrTiO3 (BST) or ZrO2 stabilized by Y. The electrodes are fabricated by Atomic Layer Deposition (ALD), which is the only approach that has been able to achieve full compliance on structures with complex shapes such as the U-shape. ALD is also the only method that could achieve thin top electrodes, however these methods reach their limits at the 100 nm technology node and must be optimized to increase capacitance density, completely fill cavities and limit current leakage.
[0003] In other semiconductor devices, such as three-dimensional integrated circuits, the metal interconnects connecting the electronic components comprise copper, which is separated from the semiconductor substrate by a layer of barrier material, such as titanium nitride and tantalum nitride, to prevent diffusion of the copper into the semiconductor substrate. To improve the performance of such devices, it is desirable to remove the barrier layer.
[0004] In WO 2021 / 219744, it has already been proposed to autocatalytically deposit an alloy of nickel and boron on metal oxides. However, this nickel alloy deposit does not produce a conductive deposit at low thicknesses, and it would be desirable to improve this technique in order to deposit an alloy layer that remains conductive (i.e., exhibits a resistivity of less than about 0.1 ohm (Ω) cm at very low thicknesses (i.e., less than 50 nm thick).
[0005] There remains a need in the art for metallization processes that allow for the deposition of thin conductive layers on substrates, such as inorganic oxide substrates, that can be used to manufacture storage memories or integrated circuits. Summary of the Invention
[0006] It is an object of the present invention to provide a method for metallizing an inorganic oxide substrate with a nickel or cobalt alloy containing at least two elements.
[0007] Another object of the present invention is to provide a method for metallizing an inorganic oxide substrate by electrolessly plating a nickel or cobalt alloy layer onto the surface of the inorganic oxide substrate.
[0008] It is yet another object of the present invention to provide a method for electroless deposition of a nickel or cobalt oxide layer onto a metal oxide layer which produces a conductive deposit at a very thin thickness.
[0009] The method of the present invention fulfills this need by providing a method for electrolessly plating a nickel alloy or a cobalt alloy onto an inorganic oxide substrate to deposit a nickel alloy or a cobalt alloy comprising boron and at least one of phosphorus and tungsten on the surface of the inorganic oxide substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In one embodiment, the present invention generally relates to a method for metallizing at least a surface of an inorganic oxide substrate by electroless plating of a nickel or cobalt alloy comprising at least two elements, the first element being boron and the second element being selected from phosphorus and tungsten. The metallization process comprises activating the surface of the inorganic oxide substrate with a precious metal, followed by contacting the surface with an electroless aqueous solution comprising nickel (or cobalt) ions, a reducing agent for the nickel (or cobalt) ions containing boron, and a compound containing at least one of phosphorus or tungsten.
[0011] As used herein, "a," "an," and "the" refer to both the singular and the plural, unless the context clearly dictates otherwise.
[0012] As used herein, the term "about" refers to a measurable value, such as a parameter, amount, duration, etc., and is meant to include no more than + / -15% variation, preferably no more than + / -10% variation, more preferably no more than + / -5% variation, even more preferably no more than + / -1% variation, and even more preferably no more than + / -0.1% variation of and from the specifically recited value, so long as such variations are appropriate to practice the invention described herein. It is further to be understood that the value to which the modifier "about" refers is itself specifically disclosed herein.
[0013] As used herein, spatially relative terms such as "beneath," "below," "lower," "above," "upper," and the like are used for ease of description to describe the relationship of one element or feature to another element(s) or feature(s) as shown in the figures. It will be further understood that the terms "front" and "back" are not intended to be limiting and are intended to be interchangeable where appropriate.
[0014] As used herein, the terms "comprises" and / or "comprising" specify the presence of stated features, integers, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof.
[0015] As used herein, the terms "substantially free" or "essentially free" with respect to a particular element or compound, unless otherwise defined herein, mean that the given element or compound is not detectable by conventional analytical means well known to those skilled in the art of metal plating for bath analysis. Such methods typically include atomic absorption spectroscopy, titration, UV-Vis spectroscopy, secondary ion mass spectrometry, and other commonly available analytical techniques.
[0016] All amounts are percent by weight unless otherwise specified. All numerical ranges are inclusive and combinable in any order, except where it is logical that such numerical ranges are constrained to add up to 100%.
[0017] The terms "composition," "bath," and "solution" are used interchangeably throughout this specification.
[0018] As used herein, the term "alloy" means a solid solution in which the elements are uniformly distributed.
[0019] In one embodiment, the alloy is a nickel alloy containing boron and at least one of phosphorous and tungsten.
[0020] In another embodiment, the alloy is a cobalt alloy containing boron and at least one of phosphorous and tungsten.
[0021] The reducing agent of nickel ions or cobalt ions containing boron is preferably in an amount sufficient for boron to account for 1 atomic % to 10 atomic % in the nickel alloy.
[0022] According to one embodiment, the nickel alloy deposited by the method of the invention is a nickel alloy containing boron and phosphorus. Boron preferably accounts for 0.1 atomic % to 10 atomic %, more preferably 0.1 to 5.0 atomic %, more preferably 0.1 to 3.0 atomic %, of the nickel alloy, and phosphorus preferably accounts for 0.1 atomic % to 10 atomic %, more preferably 0.1 to 5.0 atomic %, more preferably 0.1 to 3.0 atomic % of the nickel alloy. The presence of both boron and phosphorus in the alloy at the stated atomic % produces a deposit that is more conductive, especially at very thin thicknesses, for example less than about 50 nm, and the deposit does not show any pinholes or voids.
[0023] According to another embodiment, the nickel alloy obtained by the method described herein is a nickel alloy containing boron and tungsten. Boron preferably comprises 0.1 atomic % to 10 atomic %, more preferably 0.1 to 5.0 atomic %, more preferably 0.1 to 3.0 atomic %, and tungsten preferably comprises 1 atomic % to 10 atomic %, more preferably 2.0 to 8.0 atomic % of the nickel alloy. The presence of both boron and tungsten in the alloy at the stated atomic % produces a deposit that is more conductive, especially at very thin thicknesses, e.g., less than about 50 nm, and the deposit does not exhibit any pinholes or voids.
[0024] According to another embodiment, the alloy obtained by the method described herein is a cobalt alloy containing boron and phosphorus. Boron preferably represents 0.1 atomic % to 10 atomic %, more preferably 0.1 to 5.0 atomic %, more preferably 0.1 to 3.0 atomic %, of the cobalt alloy, and phosphorus preferably represents 0.1 atomic % to 10 atomic %, more preferably 0.1 to 5.0 atomic %, more preferably 0.1 to 3.0 atomic % of the cobalt alloy. The presence of both boron and phosphorus in the alloy in the stated atomic % produces a deposit that is more conductive, especially at very thin thicknesses, for example less than about 50 nm, and the deposit does not show any pinholes or voids.
[0025] According to another embodiment, the alloy obtained by the method described herein is a cobalt alloy containing boron and tungsten. Boron preferably comprises 0.1 atomic % to 10 atomic %, more preferably 0.1 to 5.0 atomic %, more preferably 0.1 to 3.0 atomic %, of the cobalt alloy, and tungsten preferably comprises 1.0 atomic % to 10 atomic %, more preferably 2.0 to 8.0 atomic % of the cobalt alloy. The presence of both boron and tungsten in the alloy at the stated atomic % produces a deposit that is more conductive, especially at very thin thicknesses, e.g., less than about 50 nm, and the deposit does not exhibit any pinholes or voids.
[0026] In one embodiment, a dielectric substrate, such as an inorganic oxide substrate, is activated with an activation solution containing a precious metal complex. In one embodiment, the precious metal of the precious metal complex is palladium. Other precious metals that can be used in the activation solution to activate the inorganic oxide surface include ruthenium, rhodium, osmium, iridium, platinum, gold, silver, and combinations of one or more of these.
[0027] The present application describes in particular electroless nickel or cobalt baths that can be used to carry out the above-mentioned method, comprising: For example, 10 -2 Nickel or cobalt ions at a concentration of M to 1M; b.10 -1 a reducing agent for nickel or cobalt ions, containing boron in a concentration that may range from M to 1M; c. at least one of a phosphorus-containing compound or a tungsten-containing compound, and d. An agent for adjusting the pH to a value between 6 and 11, preferably between 8 and 10.
[0028] The phosphorus-containing compound is preferably 10 -1 The concentration of the tungsten-containing compound is preferably 0.3 mM to 30 mM, preferably 1 mM to 5 mM.
[0029] The invention also relates to a three-dimensional semiconductor device obtainable by implementing the method described above.
[0030] The method of the invention is particularly applicable to achieving the filling of cavities previously formed in a semiconductor substrate, the dimensions of which at their openings are less than 5 micrometers, or less than 3 micrometers, or less than 1 micrometer, or less than 500 nm, or less than 100 nm, or less than 50 nm, or less than 25 nm, or less than 10 nm.
[0031] The method of the invention makes it possible to produce metal deposits on substrates having a complex topography in terms of relief and shape, as well as to produce metal layers on the walls of openings and cavities of small size, up to 50 micrometers, or up to 100 micrometers, or up to 200 micrometers deep, as defined above. The method of the invention makes it possible in particular to overcome the problem of copper diffusion into the layer of barrier material.
[0032] Contact of the electroless solution with the inorganic oxide surface is carried out under conditions that allow for the formation of a nickel (or cobalt) alloy layer having a thickness of, for example, about 1 to about 25 nm, more preferably about 2 to about 20 nm, more preferably at least about 4 to about 15 nm, more preferably about 5 nm to 10 nm, which nickel alloy or cobalt alloy layer is at least substantially free of pinholes and other defects. The average resistivity of the nickel (or cobalt) alloy layer is measured by a four-point probe at several locations on the plated nickel alloy or cobalt alloy surface. The average resistivity may be in the range of about 30 to 60 sub-micrometer ohm (μohm (Ω)) cm, measured at 10 to 40 nm. The resistivity of the alloy layer is preferably less than 55 μohm cm when the layer is 10 nm or less thick.
[0033] The inorganic oxide substrate may be selected from, by way of example and not limitation, silicon dioxide (SiO2), alumina (Al2O3), hafnium oxide, zirconium oxide, and silicates thereof.
[0034] In a particular embodiment, the nickel or cobalt alloy layer obtained by the method of the invention is characterized by a lower thickness, but with the same or better electrical conductivity, as the metal layer obtained according to the teachings of French Patent No. 3 109 840. In particular, the thickness of the nickel or cobalt alloy according to the invention may be less than 50 nm, or less than 40 nm, or less than 30 nm, or less than 20 nm, or less than 10 nm, and is at least substantially free of defects such as pinholes or voids.
[0035] The electrical conductivity of the nickel alloy layer obtained in accordance with the teachings of the present invention is generally in the range of about 30 to about μohm cm at a thickness of about 10 to about 40 nm.
[0036] The electrical conductivity of the cobalt-alloy layer obtained in accordance with the teachings of the present invention is typically in the range of about 35-45 μohm cm at a thickness of about 30 nm.
[0037] Surface activation can be carried out, for example, by grafting a noble metal such as palladium, according to the teachings of WO 2011 / 029860 or US 8,883,641. Other noble metals include ruthenium, rhodium, osmium, iridium, platinum, gold and silver, or combinations thereof. Surface activation of the insulating layer can also be carried out by deposition of metal nanoparticles, such as nickel-boron nanoparticles, as described in WO 2010 / 001054.
[0038] According to one embodiment, when the dielectric is an inorganic oxide, in particular SiO2 or Al2O3, activation of the surface is carried out with an activation solution containing a solvent, at least one noble metal complex, which may be a ruthenium, rhodium, osmium, iridium, palladium, platinum, gold and / or silver complex, and at least one organosilane compound. In one embodiment, the activation solution comprises a solvent, a palladium complex, and at least one organosilane compound.
[0039] The palladium complex may be selected from (NH4)2(PdCl4), Pd(NH3)4, and a complex of formula (I):
[0040] [ka] During the ceremony, R1 and R2 are the same and represent H, CH2CH2NH2, or CH2CH2OH; or R1 represents H and R2 represents CH2CH2NH2, or R1 represents CH2CH2NH2 and R2 represents CH2CH2NHCH2CH2NH2, or R1 represents H and R2 represents CH2CH2NHCH2CH2NHCH2CH2NH2; X is Cl - , Br - , I - , H2O, NO3 - , CH3SO3 - , CF3SO3 - , CH3-Ph-SO3 - , or CHCOO - represents a ligand selected from the group consisting of:
[0041] In one embodiment, the activation solution comprises 10 -6 M~10 -2 M, preferably 10 -5 M~10 -3 M, preferably 5-10 -5 M~5·10 -4 M concentration of the palladium complex.
[0042] The organosilane compound in the activation solution ensures adhesion between the nickel or cobalt alloy layer and the inorganic oxide.
[0043] According to a particular feature of the invention, the organosilane compound has the following general formula (II): {X-(L)} 3-n Si(OR) n (II) During the ceremony, X represents a functional group selected from the group consisting of thiol, pyridine, epoxy (oxacyclopropanyl), glycidyl, and simple palladium compounds or primary amines capable of reacting with formula (I); L represents a spacer arm selected from the group consisting of CH2, CH2CH2, CH2CH2CH2, CH2CH2CH2CH2-, CH2CH2NHCH2CH2, CH2CH2CH2NHCH2CH2, CH2CH2CH2NHCH2CH2, CH2CH2CH2NHCH2CH2, CH2CH2CH2NHCH2CH2CH2CH2CH2CH2CH2CH2, Ph, Ph-CH2, and CH2CH2-Ph-CH2 (Ph represents a phenyl ring); R is a group selected from the group consisting of CH3, CH3CH2, CH3CH2CH2, and (CH3)2CH; n is an integer equal to 2 or 3.
[0044] The organosilane compound may also have the general formula (III): (OR)3Si-(L)-Si(OR)3(III) During the ceremony, L represents a spacer arm selected from the group consisting of CH2CH2CH2NHCH2CH2NHCH2CH2, and CH2CH2CH2-SS-CH2CH2CH2; R is a group selected from the group consisting of CH3, CH3CH2, CH3CH2CH2, and (CH3)2CH.
[0045] The compound of general formula (II) or (III) may be selected from the following compounds: (3-aminopropyl)triethoxysilane, (3-aminopropyl)trimethoxysilane, m-aminophenyltrimethoxysilane, p-aminophenyltrimethoxysilane, p,m-aminophenyltrimethoxysilane, 4-aminobutyltriethoxysilane, m,p(aminoethylaminomethyl)phenethyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 2-(4-pyridylethyl)triethoxysilane, bis(3-trimethoxysilylpropyl)ethylenediamine, (3-trimethoxysilylpropyl)ethylenediamine, p-diethylenetriamine, ethylenediamine, N-(3-trimethoxysilylethyl)ethylenediamine, N-(6-aminohexyl)aminopropyltrimethoxysilane, (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)triethoxysilane, 5,6-epoxyhexyltriethoxysilane, (3-mercaptopropyl)trimethoxysilane, (3-mercaptopropyl)triethoxysilane, bis[3-(triethoxysilyl)propyl]disulfide, 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, (p-chloromethyl)phenyltrimethoxysilane, and m,p((chloromethyl)phenylethyl)trimethoxysilane.
[0046] Examples of preferred organosilane compounds that may be used in the practice of the present invention may include compounds of formula (II), wherein: X represents an NH2 group, L represents CH2CH2CH2- and R represents CH3 (i.e. (3-aminopropyl)-trimethoxy-silane or APTMS), or L represents CH2CH2CH2 and R represents CH3CH2 (i.e. (3-aminopropyl)-triethoxy-silane or APTES), or L represents CH2CH2NHCH2CH2 and R represents CH3 (i.e. [3-(2-aminoethyl)aminopropyl]trimethoxy-silane or DATMS or DAMO), or X represents SH, L represents CH2CH2CH2-, and R represents CH2CH3 (i.e., (3-Mercaptopropyl) trimethoxysilane or MPTES), or X represents C6H5N, L represents CH2CH2-, and R represents CH2CH3 (i.e., 2-(4-Pyridylethyl) triethoxysilane or PETES), or X represents CHCHO, L represents CHCHCH, and R represents CH (i.e., (3-Glycidoxypropyl) trimethoxysilane or EPTMS), or X represents Cl, L represents CHCHCH, and R represents CH (i.e., 3-Chloropropyltrimethoxysilane or CPTMS).
[0047] In one embodiment, the organosilane compound is (3-aminopropyl)-trimethoxy-silane (APTMS).
[0048] The concentration of the organosilane compound in the activation solution is preferably 10 -5 M~10 -1 M, preferably 10 -4 M~10 -2 M, preferably 5-10 -4 M~5·10 -3 It's M.
[0049] The solvent of the activation solution must be capable of solubilizing the compounds contained in the activation solution. This solvent system may consist of one or more solvents selected from the group consisting of N-methylpyrrolidinone (NMP), dimethyl sulfoxide (DMSO), alcohols, ethylene glycol ethers such as monoethyl-diethylene glycol (EDEG), propylene glycol ethers, dioxane and toluene. In general, the solvent system advantageously consists of a mixture of a solvent capable of solubilizing the palladium compound and a solvent such as ethylene glycol ether or propylene glycol ether. In one embodiment, a solvent system that is particularly preferred due to its very low toxicity consists of dimethyl sulfoxide (DMSO) alone or a mixture of dimethyl sulfoxide (DMSO) and monoethyl ether diethylene glycol (EDEG). These compounds may be used in a volume ratio of 1:200 to 1:5, preferably about 1:10.
[0050] In one embodiment, the activation solution for activating inorganic oxide surfaces is a palladium complex with ethylenediamine and aminopropyl trimethoxy-silane (APTMS).
[0051] Once the inorganic oxide surface has been activated with the activating solution, the activated inorganic oxide surface may be contacted with an electroless metal alloy plating solution as further defined herein.
[0052] In the case of electroless nickel solutions, nickel ions are introduced into the electroless solution by dissolving a nickel metal salt. In one embodiment, the nickel salt is selected from the group consisting of acetate, acetylacetonate, hexafluorophosphate, nitrate, perchlorate, sulfate, or nickel tetrafluoroborate. A hydrated form of one of the listed nickel salts may also be used. In one embodiment, the salt is nickel sulfate hexahydrate. The nickel ions may be, for example, 10 -2 The concentration is from 50 mM to 1M, preferably from 50 mM to 500 mM.
[0053] In the case of electroless cobalt solutions, the cobalt ions are introduced into the electroless solution as inorganic cobalt salts, such as chlorides and / or sulfates, or other inorganic salts or complexes, such as pyrophosphates, or cobalt complexes with organic carboxylates, such as acetates, citrates, lactates, succinates, propionates, and hydroxyacetates. -2 The concentration is from 50 mM to 1M, preferably from 50 mM to 500 mM.
[0054] The boron-containing reducing agent may be a borane derivative, such as a borane derivative selected from dimethylaminoborane, pyridine borane, morpholene borane, and tertbutylamine borane.
[0055] The compound containing phosphorus as a doping element may be hypophosphorous acid or one of its salts, such as sodium hypophosphite or magnesium hypophosphite. The compound containing phosphorus as a doping element is, for example, at a concentration of 10 mM to 1 M, preferably 400 mM to 600 mM.
[0056] The compound containing tungsten as a doping element may be, for example, a tungstate such as sodium tungstate, calcium tungstate, or ammonium tungstate. The compound containing tungsten as a doping element has a concentration of, for example, 0.3 mM to 30 mM, preferably 1 mM to 5 mM.
[0057] The electroless solution contains at least one nickel ion or cobalt alloy stabilizer, preferably at least 10 -3 Preferably, the compound is present in an amount of about 0.1M to 1M, more preferably about 0.1M to 1M.
[0058] The optional nickel or cobalt ion stabilizer may be selected from the group consisting of ethylenediamine, citric acid, acetic acid, succinic acid, malonic acid, aminoacetic acid, malic acid or the alkali metal salts of these compounds. In one embodiment, the nickel or cobalt ion stabilizer comprises citric acid, which forms a complex with the nickel or cobalt ions in solution.
[0059] The aqueous electroless solution may also include a pH adjuster to adjust the pH to a value between 6 and 11. In one embodiment, the pH of the aqueous solution ranges from 8 to 10, more preferably from 9.0 to 9.5. The pH adjuster may be selected from the group consisting of aminoethanol, N-methylaminoethanol, and N,N-dimethylaminoethanol. A preferred pH adjuster is N-methylaminoethanol.
[0060] The electroless plating solution may also contain a polyamine, preferably an aliphatic polyamine, in a concentration that may be from 5 ppm to 1000 ppm (mg / L), more preferably from about 10 to about 100 ppm.
[0061] In a preferred embodiment, the electroless solution contains a polyamine, preferably a polyethyleneimine, preferably having a molecular weight of 500 g / mol or greater, more preferably greater than about 600 g / mol, more preferably greater than about 700 g / mol.
[0062] Alternatively, the solution may contain a polymer selected from chitosan, poly(allyl-amine), poly(vinyl-amine), poly(vinyl-pyridine), poly(amino-styrene), poly(L-lysine) derivatives, and the acid (or protonated) forms of these polymers.
[0063] The contact of the substrate with the electroless solution can be carried out by immersing the inorganic oxide substrate in the above-mentioned solution for 30 seconds to 15 minutes, more preferably about 1 minute to about 10 minutes, at a temperature of 40° C. to 90° C., preferably 60° C. to 70° C., depending on the thickness of the nickel alloy desired. The contact with the electroless solution is advantageously carried out for a sufficient time to obtain a nickel alloy layer or a cobalt alloy layer having a thickness of more than 1 nm to less than 25 nm, more preferably 4 nm or more to 10 nm or less.
[0064] The deposition step of the alloy metal layer can be carried out under different process conditions. For example, in one embodiment, the substrate to be coated can be rotated. In another embodiment, a recirculation of the electroless solution can be imposed in the reactor. In another embodiment, the contact of the substrate with the electroless solution can be carried out by spraying the solution at high pressure. Other means can also be used in a complementary manner, for example by vibrating the substrate and / or the solution using ultrasound or megasound. In all cases, the contact can be carried out under vacuum. The surface to be coated can be placed face up or face down.
[0065] According to an advantageous embodiment, the electroless nickel alloy or cobalt alloy layer may be annealed at a temperature between 200° C. and 700° C., preferably between 350° C. and 450° C., for a period between 1 minute and 30 minutes, preferably between about 5 minutes and about 15 minutes, more preferably about 10 minutes, in an inert or reducing atmosphere (e.g., 4% hydrogen in nitrogen).
[0066] The present application describes an electroless solution comprising: a) 10 -2 M to 1M, preferably 50 mM to 500 mM, of nickel ions or cobalt ions; b) 10 -1 M to 1M, preferably 400 mM to 600 mM, of at least one reducing agent containing boron; c) 10 -1M to 1M, preferably 400 mM to 600 mM, of a phosphorus-containing compound, preferably hypophosphorous acid or salt, or 0.3 mM to 30 mM of a tungsten-containing compound, preferably tungstate, d) optionally, one or more nickel ion stabilizers or cobalt ion stabilizers; d) optionally a pH adjuster; e) 5 mg / L to 1000 mg / L (or ppm) of an amino polymer, preferably polyethyleneimine, more preferably having a molecular weight in the range of 500 to 25,000 g / mol, more preferably about 600 to about 20,000 g / mol, more preferably about 700 to about 15,000 g / mol, more preferably about 800 to about 10,000 g / mol, more preferably about 1,000 to about 5,000 g / mol, and residual water.
[0067] In one embodiment, the electroless solution consists essentially of the recited components. By "consisting essentially of," it is meant that the electroless solution does not contain any components that detrimentally affect electrical conductivity, including concentrations of boron, phosphorous, and / or tungsten above the ranges defined herein.
[0068] In one embodiment, the electroless solution is comprised of the ingredients listed to provide an electroless nickel or cobalt alloy layer on an inorganic oxide substrate that exhibits good electrical conductivity at very low thicknesses.
[0069] The molar ratio of boron to phosphorus in the electroless solution is preferably 1 / 10 to 10 / 1, more preferably 1 / 5 to 5 / 1, and more preferably 1 / 2 to 2 / 1.
[0070] The molar ratio of boron to tungsten in the electroless solution is preferably 10 / 1 to 500 / 1, preferably 50 / 1 to 300 / 1, preferably 100 / 1 to 200 / 1.
[0071] The metal processing method of the present invention can be used in the manufacture of three-dimensional semiconductor devices such as three-dimensional integrated circuits or 3D-NAND type storage memories at the level of creating copper conductive lines, or MIM capacitors forming part of the structure of V-DRAM or DRAM storage memories.
[0072] The invention also generally relates to semiconductor devices obtained by implementing the above-mentioned method or electrolyte.
[0073] The present application also describes a three-dimensional semiconductor device comprising a thin layer of an alloy of nickel, boron and phosphorus, comprising 1% to 10% atomic, preferably 1% to 7% atomic, boron, and 1% to 10% atomic, preferably 1% to 7% atomic, phosphorus, deposited on an inorganic oxide surface.
[0074] The present application further describes a three-dimensional semiconductor device comprising a thin layer of an alloy of nickel, boron and tungsten, comprising 1% to 10% atomic, preferably 1% to 7% atomic, boron, and 1% to 10% atomic, preferably 1% to 7% atomic, tungsten, deposited on an inorganic oxide surface. Thus, the metal processing method of the present invention may be used in the manufacture of copper conductive lines, comprising depositing a nickel alloy layer on the walls of cavities in an inorganic oxide that are intended to be filled with copper in a subsequent processing step.
[0075] The present application also describes a three-dimensional semiconductor device comprising a thin layer of an alloy of cobalt, boron and phosphorus, comprising 1% to 10% atomic, preferably 1% to 7% atomic, boron, and 1% to 10% atomic, preferably 1% to 7% atomic, phosphorus, deposited on an inorganic oxide surface.
[0076] The present application further describes a three-dimensional semiconductor device comprising a thin layer of an alloy of cobalt, boron and tungsten, comprising 1% to 10% atomic, preferably 1% to 7% atomic, boron, and 1% to 10% atomic, preferably 1% to 7% atomic, tungsten, deposited on an inorganic oxide surface. Thus, the metal processing method of the present invention may be used in the manufacture of copper conductive lines, comprising depositing a cobalt alloy layer on the walls of cavities in an inorganic oxide that are intended to be filled with copper in a subsequent processing step.
[0077] These cavities may, for example, have an average diameter at the opening in the range of 10 nm to 30 nm and a depth in the range of 20 nm to 100 nm. The average diameter at the opening of the cavities is preferably less than 500 nm, for example less than 400 nm, or less than 300 nm, or less than 200 nm, or less than 100 nm, or less than 50 nm, or less than 10 nm.
[0078] The invention will now be described with reference to the following non-limiting examples.
[0079] Example 1: Deposition of a thin layer of nickel-boron-phosphorus alloy on the walls of a cavity In this example, the substrate used is a SiO2 coupon, 4 cm x 4 cm sides and 750 μm thick, with a vertical cavity with an opening of about 10 μm and a height of about 100 micrometers.
[0080] (a) Cleaning of cavity surfaces: The specimens are cleaned according to the chemistry of the substrate. After this cleaning step, the specimens are rinsed thoroughly with deionized water, immersed in a beaker filled with deionized water, and subjected to ultrasound (40 kHz) for 2 minutes.
[0081] b) Activation of the cavity surface: b1) Preparation of the activation solution: In a beaker, 350 microliters of (3-aminopropyl)-trimethoxysilane (APTMS) and 15 mg of Pd(ethylenediamine)Cl2 are dissolved in 80 ml of dry DMSO (max 50 ppm or mg / L H2O).
[0082] (b2) Substrate surface activation treatment: The test specimen prepared in step a1) is immersed in a beaker containing the activation solution prepared in b1) at a temperature of 65° C. for 15 minutes under ultrasound. The test specimen is removed from the solution, rinsed thoroughly with deionized water, immersed in a beaker filled with deionized water and subjected to ultrasound (40 kHz) for 30 seconds. Finally, the test specimen is removed from the beaker and rinsed thoroughly with deionized water.
[0083] c) Deposition of a layer of metallic NiB by electroless plating: c1) Pre-preparation of the electroless solution: In a 1 liter vessel, 31.11 g of nickel sulfate hexahydrate (0.118 mol), 44.67 g of citric acid (0.232 mol), 52.26 g of N-methylaminoethanol (0.700 mol), 25 ppm of polyethyleneimine (PEI) with Mn=600 g / mol, and 6 ml of 50% hypophosphorous acid (0.475 mol) are introduced in this order. The final pH is adjusted to 9.3 with N-methylaminoethanol and the total volume is adjusted to 1 liter with deionized water. To the 9 volumes of the previous solution, a volume of reducing solution is added immediately before the next step. The latter contains 28 g / L of dimethylaminoborane (DMAB, 0.475 mol) and 60.00 g of N-methylaminoethanol (0.798 mol).
[0084] c2) Forming a NiB alloy layer on the alumina layer: A nickel-boron alloy layer is deposited on the surface of the substrate treated in step b) by first immersing the substrate in a beaker of deionized water and then immersing the substrate for 2 minutes in a pre-prepared electroless solution heated to 65°C. A grey, shiny metal cover is then observed on the specimen. The specimen is removed from the solution, rinsed thoroughly with deionized water, immersed in a beaker filled with deionized water and subjected to ultrasound (40 kHz) for 30 seconds. Finally, the specimen is removed from the beaker, rinsed thoroughly with deionized water and dried under a nitrogen flow. The specimen is subjected to Rapid Thermal Annealing (RTA) at 400°C for 10 minutes in a reducing atmosphere (4% hydrogen in nitrogen). The operation can be carried out using a tubular oven or a hot plate.
[0085] (d) Characteristics of the metal deposit filling the cavity The vertical cavity is coated with a thin layer of nickel alloy containing boron and phosphorus. The thickness of the nickel layer measured under a microscope at 150,000x magnification ranged from 7nm to 10nm across the sample. The electrical conductivity measured with a four-point probe at different points in the sample ranged from 35 to 60μohm cm.
[0086] Comparative Example 2: Example 1 was reproduced with the difference that in step c1), the concentration of hypophosphorous acid was reduced to 0.0475 molar and the concentration of PEI was reduced to 2.5 ppm.
[0087] The walls of the vertical cavity are covered with a thin layer of nickel-boron alloy containing less than 1% atomic phosphorus, the thickness of which is observed to be in the range of 7 nm to 10 nm as measured under a microscope at 150,000 times magnification. The resistivity was in the range of 65 to 120 μohm cm. The resulting nickel alloy deposit is more resistive, less dense, less compact, and more defective than the deposit obtained in Example 1 using the method of the present invention. This example demonstrates that although trace amounts of phosphorus in an electroless nickel plating bath can produce nickel deposits, the resulting nickel deposits do not exhibit good properties at the desired thicknesses of the present invention. Similarly, this example also shows that the use of PEI in concentrations in the ranges described by the present invention also aids in the production of electroless nickel deposits exhibiting desired properties.
[0088] Example 3: Deposition of thin layers of nickel-boron-tungsten alloy Example 1 was reproduced with the difference that in step c1), 0.475 moles of hypophosphorous acid were replaced by 3 mM of sodium tungstate dihydrate. The vertical cavity was covered with a continuous layer of nickel alloy containing boron and tungsten, which was dense and compact with a resistivity equal to 30 μohm cm, thereby improving the conductivity by 25% when the layer thickness was less than 10 nm.
Claims
1. 1. A process for metallizing at least a surface of an inorganic oxide substrate with a nickel or cobalt alloy comprising at least two elements, the first element being boron and the second element being selected from phosphorus and tungsten, the metallization process comprising: a) activating the surface of the inorganic oxide substrate with a precious metal activating solution, followed by and b) contacting the surface of the inorganic oxide substrate with an electroless nickel or cobalt solution to form the nickel or cobalt alloy, the electroless solution comprising: i) nickel or cobalt ions; ii) a nickel or cobalt ion reducing agent comprising boron; and iii) a compound comprising a doping element selected from phosphorous and tungsten, the compound comprising the doping element being in an amount sufficient such that the dopant element represents 1 atomic % to 10 atomic % of the nickel alloy.
2. 2. The process according to claim 1, characterized in that the molar ratio of boron to phosphorus in the electroless solution is between 1 / 10 and 10 / 1, preferably between 1 / 5 and 5 / 1, preferably between 1 / 2 and 2 / 1.
3. 2. The process according to claim 1, characterized in that the molar ratio of boron to tungsten in the electroless solution is between 10 / 1 and 500 / 1, preferably between 50 / 1 and 300 / 1, preferably between 100 / 1 and 200 / 1.
4. The nickel ion or the cobalt ion is 10 -2 The process according to any of claims 1 to 3, characterized in that the concentration is between 50 mM and 500 mM.
5. A process according to any of claims 1 to 4, characterized in that the compound containing phosphorus as doping element is at a concentration between 10 mM and 1 M, preferably between 400 mM and 600 mM.
6. 6. The process according to claim 1, characterized in that the compound containing phosphorus as doping element is selected from hypophosphorous acid and its salts.
7. 7. The process according to claim 6, characterized in that the compound containing phosphorus as doping element is selected from the group consisting of hypophosphorous acid, sodium hypophosphite or magnesium hypophosphite.
8. A process according to any of claims 1 to 4, characterized in that the compound containing tungsten as doping element is in a concentration between 0.3 mM and 30 mM, preferably between 1 mM and 5 mM.
9. 9. The process according to claim 1 or 8, characterized in that the compound containing tungsten as doping element is a tungstate.
10. 10. The process of claim 9, wherein the tungstate is selected from the group consisting of sodium tungstate, calcium tungstate, and ammonium tungstate.
11. The process according to any one of claims 1 to 10, characterized in that the contacting with the electroless solution is carried out for a time sufficient to obtain a nickel-alloy or cobalt-alloy layer having a thickness of 10 nm or less.
12. 12. The process of any one of claims 1 to 11, characterized in that the reducing agent of nickel or cobalt ions containing boron is in an amount sufficient such that boron accounts for 1 atomic % to 10 atomic % in the nickel or cobalt alloy.
13. 13. The process according to any one of claims 1 to 12, characterized in that the nickel ion reducing agent or the cobalt ion reducing agent is dimethylaminoborane.
14. The inorganic oxide substrate is SiO 2 Or Al 2 O 3 The process according to any one of claims 1 to 13, characterized in that
15. The process according to any one of claims 1 to 14, characterized in that the precious metal contained in the precious metal activation solution is palladium.
16. 16. The process of claim 15, wherein the activation solution comprises a solvent, a palladium complex, and an organosilane compound.
17. A process according to any one of the preceding claims, characterized in that the electroless nickel or cobalt solution comprises a pH adjuster for adjusting the pH to a value between 6 and 11, preferably between 8 and 10.
18. The process according to any one of claims 1 to 17, characterized in that the electroless nickel or cobalt solution contains from 5 ppm to 1,000 ppm of a polyamine.
19. The process according to any of claims 1 to 18, further comprising a step of rapid thermal annealing of the nickel alloy layer or the cobalt alloy layer formed on the surface of the inorganic oxide substrate.
20. A three-dimensional semiconductor device obtainable by the process according to any one of claims 1 to 19.